Energy value of babassu cake as substitute bulk in sheep diets - Castro, Kélvia Jácome de; Gomes, Silas Primola; Borges, Iran; Miotto, Fabrícia Rocha Chaves; Pimentel, Patrícia Guimarães; Pinto, Andréa Pereira; Moreira, Guilherme Rocha; Neiva, José Neuman Miranda (Semina: Ciências Agrárias, 2021)
The aim of this study was to evaluate the energy value of diets containing babassu cake as a replacement for Tifton-85 hay (70, 140, 210, 280 and 350 g kg-1 dry matter, DM), using the technique of indirect calorimetry. Twenty-five castrated male Santa Inês sheep, with an average body weight of 49.6 + 9.4 kg, were used in a completely randomised design. The trial was carried out in an individual open-flow respirometry chamber for small ruminants, with each animal remaining for 24 hours inside the chamber. Gross energy and net energy intake were not affected by adding the cake. Digestible energy intake and metabolisable energy intake showed a linear response, ranging from 145.44 to 178.40 and from 121.85 to 158.08 kcal kg-0.75 day-1 respectively. The energy lost through faeces and methane (% of gross energy intake, GEI) showed decreasing linear behaviour, while the caloric increase, in %GEI, showed a quadratic response. The values for digestible energy and metabolisability presented an increasing linear response. The partial efficiency of use of metabolisable energy for maintenance ranged from 0.71 to 0.81, and showed a quadratic response; however, the net energy values did not differ. For every 10 g of added by-product, there was a reduction of 0.31 g of methane per kg of DM intake. The addition of babassu cake to replace up to 350 g kg-1 DM in sheep diets increases the energy efficiency of the diet and reduces methane emission by the animals.